Neuroendocrine Differentiation and Epithelial to Mesenchymal Transition in Prostate Cancer: cAMP-Dependent Signaling as a Therapeutic Target (Journal of Analytical Oncology, 2015)
Prostate cancer exhibits both epithelial to mesenchymal transition and neuroendocrine differentiation. The major barrier to targeting epithelial to mesenchymal transition is that it is heavily involved with normal biology, such as wound repair. In prostate cancer, cAMP can trigger both neuroendocrine differentiation and epithelial to mesenchymal transition in a Snail-dependent manner We will review inhibition of cAMP-signaling as a target for drug development with the goal of simultaneously blocking both neuroendocrine differentiation and epithelial to mesenchymal transition in a tissue and tumor selective manner.